PENDIDIKAN KARAKTER DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Maulana Yusuf (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACSome of the problems concerning the character of children that often arise in society include violence, fights, promiscuity, hedonistic and consumptive lifestyles, and so on. Character education is an alternative to solving children's character problems that are preventive and curative. The purpose of writing this article is to find out more about character education in the perspective of Islamic education philosophy. Literature study used in article writing. Based on the discussion in this article, it can be concluded that in the perspective of Islamic education, character education developed by the Ministry of Education is very relevant to character education taught in Islamic education. The values taught in character education (18) as developed by the Ministry of Education mostly contain morals or morals which are also taught in character education within the scope of Islamic education. Some of the character values taught in Islamic education include siddiq, amanah, tabligh and fathanah. Not only that, character education taught in Islamic education also includes attitudes or characters that are based on the noble qualities of Allah (Asmaul Husna) such as compassion, forgiveness, respect, glorifying others, weak, polite, likes, likes, wise, caring, fair, beneficial and patient. These characters are expected to be possessed by every student after they take Islamic education and can apply these characters in society.